Oropouche fever outbreak is emerging concern in American countries - Roney, Miah; Mohd Fadhlizil Fasihi, Mohd Aluwi (Springer Nature, 2024)
The Oropouche virus (OROV) is the segmented single-stranded RNA virus of the genus Orthobunyavirus, a developing arboviral ailment that is the cause of the Oropouche fever (OROF) (Zhang et al. 2024). It is spread to people by the bite of certain Culex quinquefasciatus mosquitoes or the Culicoides paraensis midge, which is typically found in wooded regions and near water bodies (Sick et al. 2019). It is believed that there are two cycles of viral circulation: epidemic and sylvatic. In the sylvatic cycle, vertebrate hosts may include birds, sloths, and monkeys (WHO 2024; Sakkas et al. 2018). Furthermore, OROV was first detected in Trinidad and Tobago in 1955 in the blood of a forest worker who had a fever. Moreover, it was found that the virus first appeared in Brazil in 1960. Significantly, OROV epidemic with an estimated 11,000 patients was recorded in Belém City, Pará State, in 1961 (Da Rosa et al. 2017). Approximately, thousands of cases have been documented in many urban epidemics in the Brazilian states of Para, Amapa, and Amazonas (WHO 2024; Sakkas et al. 2018). OROF has been a prominent source of arboviral infection, especially in the Latin American Amazon area (Sakkas et al. 2018; Da Rosa et al. 2017; Moreira et al. 2024). It is also widely distributed in the Caribbean, Central America, and South America (de Thoisy et al. 2024).